2004
DOI: 10.1021/es0301018
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Separate Urine Collection on Advanced Nutrient Removal Processes

Abstract: Municipal wastewater contains a mixture of minerals from different origins. Urine contributes 80% of the nitrogen (N) and 45% of the phosphate (P) load in wastewater. Effects of separate urine collection on BNR processes were evaluated by using a simulation model for an existing stateof-the-art biological nutrient removal process. It was found that increasing urine separation efficiency leads to lower nitrate effluent concentrations, while ammonium and phosphorus concentrations remain more or less the same. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
28
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 69 publications
(30 citation statements)
references
References 20 publications
(27 reference statements)
0
28
0
Order By: Relevance
“…In particular, the highly concentrated urine stream contributes about 85% of nitrogen, 50% of phosphorus, and 55% of potassium to the domestic wastewater but only 1% of the total volume (Larsen and Gujer, 1996;Meinzinger and Oldenburg, 2009). It is therefore acceptable to seek separate urine collection, which may significantly decrease the discharge of nutrients into water bodies and prolong the longevity of existing wastewater treatment plants (Wilsenach and Van Loosdrecht, 2004). Besides, the separate treatment of micropollutants contained in urine appears to be an additional merit of the source separation system (Winker et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…In particular, the highly concentrated urine stream contributes about 85% of nitrogen, 50% of phosphorus, and 55% of potassium to the domestic wastewater but only 1% of the total volume (Larsen and Gujer, 1996;Meinzinger and Oldenburg, 2009). It is therefore acceptable to seek separate urine collection, which may significantly decrease the discharge of nutrients into water bodies and prolong the longevity of existing wastewater treatment plants (Wilsenach and Van Loosdrecht, 2004). Besides, the separate treatment of micropollutants contained in urine appears to be an additional merit of the source separation system (Winker et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…One may also want to extend the life time of an existing, overloaded treatment plant, either by peak shaving (Rauch et al, 2003) or by separating advanced nutrient elimination from removal of organic matter (Wilsenach and van Loosdrecht, 2004). If NoMix technology shall rely on local storage and subsequent transport of urine in combined sewers as first suggested by Larsen and Gujer (1996) (for explanations see below), avoiding urine in CSOs is of special importance, and storage capacity must be optimized in order to avoid transport during rain.…”
Section: Introductionmentioning
confidence: 99%
“…Source separation of urine not only offers improved conservation of water quality but also water quantity. Various studies by Larsen & Gujer (1996, Jonsson & Vinnerâs (2007), Wilsenach & van Loosdrecht (2004), Wilsenach et al (2003Wilsenach et al ( , 2007Wilsenach et al ( , 2009) and Larsen & Lienert (2007) show that source separation of urine with separate treatment and nutrient recovery can bring significant surface water benefits (quality improvement and quantity savings) and unlock greater treatment capacity at existing WWTPs, all aspects aligned with greater sustainability of urban water and sanitation systems.…”
Section: Source Separation Of Urine Can Improve Surface Water Quaiitymentioning
confidence: 99%
“…This implies that with separate urine collection, the flow of wastewater to WWTPs will be less by about 351/(p,d) (ignoring the volume of urine per person) or about 15% hence leading to an increase in brown water that can be treated. Even though the BNRAS reactor volume is governed by the sludge age and organic (and inorganic) load on the WWTP, the reduced hydraulic load does create additional WWTP capacity by reducing the overflow rate in the secondary settling tanks, Wilsenach & van Loosdrecht (2004) found that a capacity increase of 40% can be achieved.…”
Section: Reduced Hydraulic Loadmentioning
confidence: 99%